Data for global lysine-acetylation analysis in rice (Oryza sativa) - Xiong, Yehui (Data Brief, 2016)
Rice is one of the most important crops for human consumption and is a staple food for over half of the world׳s population (Yu et al., 2002) [1]. A systematic identification of the lysine acetylome was performed by our research (Xiong et al., 2016) [2]. Rice plant samples were collected from 5 weeks old seedlings (Oryza sativa, Nipponbare). After the trypsin digestion and immunoaffinity precipitation, LC–MS/MS approach was used to identify acetylated peptides. After the collected MS/MS data procession and GO annotation, the InterProScan was used to annotate protein domain. Subcellular localization of the identified acetylated proteins was predicted by WoLF PSORT. The KEGG pathway database was used to annotate identified acetylated protein interactions, reactions, and relations. The data, supplied in this article, are related to “A comprehensive catalog of the lysine-acetylation targets in rice (O. sativa) based on proteomic analyses” by Xiong et al. (2016) [2].